Ultrasonic motion detector with 180° rotational security camera / Mohd Syahir Ramli - Ramli, Mohd Syahir (2007)
This project is a development of security camera to increase the security system by implement the Ultrasonic Motion Detector with the security camera which alert to any movement for 180° rotational. It is a fully automated security camera that being programmed from PIC Microcontroller chip to control the Futaba S3003 servo motor. The instructions that programmed inside the chip will read the low signal from the output detector circuit and send a signal to move the servo motor according to the angular of motion position required. The servo angle is determined by the low pulse send from 3 different position of detector circuit. Once the microcontroller received the pulse, the security camera that mount by the servo motor will turn to the direction. If the motion move more than 1 minute or the motion detect more than 1 angle, the alarm and the porch light will turn ON to alert the house owner even before the intruder can access into the house. Once the alarm or the porch light turn ON, it will scare away the intruder or make them think more than twice to rob. The system is more practical for residential houses where the yard areas are wider compare to the flat house.